Status, Challenges and Opportunities of Distribution among Beverage Products - Andias, Amiel B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examined the status, challenges, and opportunities for beverage product distribution in Dipolog and Dapitan, Zamboanga del Norte. The study involved 30 merchants and distributors and employed a mixed-methods approach of research, which included quantitative surveys and in-depth interviews. It investigated their characteristics (size, type, and years of operation), sales performance, and distribution status. The study revealed that the retailer/distributors categorized by business size into micro (50.0%), small (20.0%), and medium (30.0%). The majority of distributors are retailers (60.0%), followed by direct distributors (20.0%), indirect distributors, and wholesalers (10.0% each). A significant portion of distributors has been in business for 5 years or less (60.0%). Sales status revealed that distributors generally agree on the frequency of sales, volume-based discounts, and the availability of credit purchases. However, there is disagreement regarding the rapidity of sales and the use of promotional activities. Challenges identified include product returns, non-collection of receivables, product expiration, and delays due to increased demand, while geographical location was less of a concern. In contrast, distributors strongly agree on several opportunities, including the potential for increased sales volume, heightened product demand, establishment of new retail stores, creation of employment, and financial stability. Despite facing various challenges, distributors are optimistic about their growth prospects. Generally, the result of the study indicates a positive outlook towards sales, with an average weighted mean of 3.35, reflecting agreement with the current sales status, challenges, and opportunities. Key challenges include market saturation, competition, and logistical issues, while opportunities highlight significant growth potential and stability. The study will be the tool in improving and constructing policies on how to improved, navigate and protect the small and medium enterprises particularly the distributors of beverage products so that they will sustain and survived in the saturated market and the law makers able to protect them in their operation. Also to the future researchers able to gauge the result of their study in the future and the result of this study this present time. Further the study will help boost local distributors' economic activity, produce revenue for local government entities lastly it will support local employment creation.